Strategic Model for Halal Tourism Development in Indonesia: A Preliminary Research - Huda, Nurul; Rini, Nova; Muslikh, Muslikh; Hidayat, Slamet; Takidah, Erika; Sari, Dian Permata; Husniyah, Af'idatul (UIN Sunan Gunung Djati Bandung, 2022)
Halal tourism is one of the emerging sectors in the halal industry. The article aims to identify the main problems, solutions, and strategies for developing a model of halal tourism. The qualitative and quantitative approaches are used in this article, including in-depth interviews and expert group discussions with the community leaders, academics, culinary and travel entrepreneurs, local tourism board, hotel entrepreneurs, and tourists representing halal tourism stakeholders. The data was complemented with research questionnaires and compiled using the Analytic Network Process (ANP) method, with Super Decision as a data processing tool. The article provides empirical insights into halal tourism in Indonesia, focusing on the root cause, the outcome of solutions, and the formulation of a future development strategy. Government-related issues remain the main priority, followed by community and halal facilities entrepreneur issues (hotel, travel, and halal food). The results showed that the priority problem in developing halal tourism in Indonesia is infrastructure problems. The solution is to build adequate road infrastructure, repair damaged roads, and complete road direction to halal tourism locations in every region of Indonesia. Halal tourism goals in Indonesia can be realized by implementing a functional synergy between the government and the local community.